Giant torturous left circumflex artery draining to the right atrium - Eremiasova, Lenka; Kuchynka, Petr; Lambert, Lukas; Palecek, Tomas (Echocardiography (Mount Kisco, N.Y.), 2017)
Coronary artery anomalies represent a diverse group of congenital disorders characterized by abnormalities of coronary arteries anatomy. We describe an extremely rare case of giant torturous left circumflex artery draining to the right atrium manifesting by palpitations and atrial fibrillation.
Keywords: Coronary Angiography; Tomography, X-Ray Computed; anomálie koronárních cév; Echocardiography, Transesophageal; Humans; diferenciální diagnóza; Heart Atria; coronary artery fistula; echocardiography; echokardiografie transezofageální; koronární cévy; mužské pohlaví; Coronary Vessel Anomalies; Severity of Illness Index; stupeň závažnosti nemoci; Diagnosis, Differential; srdeční síně; lidé; computed tomography; Coronary Vessels; počítačová rentgenová tomografie; Aged; senioři; Male; koronární angiografie